Recommendations and technical specifications for sustainable surveillance of zoonotic pathogens where wildlife is implicated. Issue 1 (12th January 2023) - ,; Gavier‐Widen, Dolores; Ferroglio, Ezio; Smith, Graham; Gonçalves, Catarina; Vada, Rachele; Zanet, Stefania; Gethöffer, Friederike; Keuling, Oliver; Staubach, Christoph; Sauter‐Louis, Carola; Blanco, Jose Antonio; et al.
Abstract: A science‐based participatory process guided by EFSA identified 10 priority zoonotic pathogens for future One Health surveillance in Europe: highly pathogenic avian influenza, swine influenza, West Nile disease, tick‐borne‐encephalitis, echinococcosis, Crimean Congo Haemorrhagic Fever, hepatitis E, Lyme disease, Q‐fever, Rift Valley fever. The main aim of this report is to formulate recommendations and technical specifications for sustainable coordinated One health surveillance for early detection of these zoonotic pathogens where wildlife is implicated. For this purpose: (i) first, we reviewed the cornerstones of integrated wildlife monitoring that are applicable to zoonotic disease surveillance in wildlife under OH surveillance in the EU; (ii) we analysed the characteristics of the main wildlife groups and the selected pathogens relevant to surveillance aimed at early detection, and integrated with other health compartments; (iii) we proposed general recommendations for the first steps of sustainable wildlife zoonotic disease surveillance in the EU, and (iv) specific recommendations of surveillance aimed at risk based early detection of pathogens in the main wild species groups. We finally proposed (iv) a framework for integrating animal disease surveillance components (wildlife, domestic, environment) for early detection under OH approach.